New Tax Issues Arising From the Dodd-Frank Act and Related Changes to Market Practice for Derivatives - Nijenhuis, Erika W. (Columbia Journal of Tax Law, 2011)
The Dodd-Frank Wall Street Reform and Consumer Protection Act (“Dodd-Frank”) requires that most over-the-counter (“OTC”) derivatives be cleared through a clearinghouse and traded on a regulated exchange. This article discusses a number of U.S. federal income tax issues raised by Dodd-Frank and related changes to market practice for derivatives. The article also provides background discussion on current market practice and the clearing process. The first question addressed by the article is the extent to which formerly-OTC derivatives traded on an exchange will become subject to the special mark-to-market rules of § 1256 that apply to other exchange-traded derivatives. Dodd-Frank partially addresses this issue through an amendment to § 1256 excluding certain types of OTC swaps from its scope. The article discusses a range of possible interpretations of this amendment and suggests some further amendments to the law that could alleviate pressure on the guidance process. The second set of tax issues addressed by this article are those stemming from the fact that the move towards regulated clearing and trading has the effect of increasing substantially the number of swaps that are entered into, or deemed entered into, with upfront payments, which may be treated under long-standing rules as giving rise to a deemed loan between the parties. The article explains the ambiguities of these rules, particularly with respect to centrally cleared swaps and in the case of credit default swaps, and suggests a number of changes to the law.